Theoretical Study of Electronic and Thermoelectric Properties of Sodium Doped 4H-GaN Polytype - M. Torrichi (Algerian Journal of Research and Technology (AJRT), 2021)
In this work, the electronic and thermoelectric properties of co-doped 4H-GaN polytype with (Na-Na) are studied using Quantum Espresso code based on norm-Conserving pseudo potential. The exchange-correlation energy was treated under the Generalized Gradient Approximation (GGA).It is interesting to note that the calculated band structure of sin up state shows a direct band gap (Γ- Γ) semiconductor with a small direct band gap (0.023 eV). While spin down state shows a metallic behavior. It indicates that 4H-GaN:Na-Na is found to be half-metallic ferromagnetic with total magnetic moment of 4.00µB. The transport properties of this material are studied using the semi-classical Boltzmann theory implanted in the BoltzTraP code. The electrical conductivity, the beck coefficient, the electronic thermal conductivity, the electronic power factor and the merit factor, as a function of temperature at fixed chemical potential were obtained for this polytype. The ZT values found for this co-doped polytype at 400K temperature are 1.01 and 0.03 respectively for spin up and down states. We therefore expect these alloys to be potential candidates for the thermoelectric applications.